Sulfur driven nucleation mode formation in diesel exhaust under transient driving conditions - Karjalainen, Panu; Rönkkö, Topi; Pirjola, Liisa; Heikkilä, Juha; Happonen, Matti; Arnold, Frank; Rothe, Dieter; Bielaczyc, Piotr; Keskinen, Jorma (Environmental science & technology, 2014)
Sulfur driven diesel exhaust nucleation particle formation processes were studied in an aerosol laboratory, on engine dynamometers, and on the road. All test engines were equipped with a combination of a diesel oxidation catalyst (DOC) and a partial diesel particulate filter (pDPF). At steady operating conditions, the formation of semivolatile nucleation particles directly depended on SO2 conversion in the catalyst. The nucleation particle emission was most significant after a rapid increase in engine load and exhaust gas temperature. Results indicate that the nucleation particle formation at transient driving conditions does not require compounds such as hydrocarbons or sulfated hydrocarbons, however, it cannot be explained only by the nucleation of sulfuric acid. A real-world exhaust study with a heavy duty diesel truck showed that the nucleation particle formation occurs even with ultralow sulfur diesel fuel, even at downhill driving conditions, and that nucleation particles can contribute 60% of total particle number emissions. In general, due to sulfur storage and release within the exhaust aftertreatment systems and transients in driving, emissions of nucleation particles can even be the dominant part of modern diesel vehicle exhaust particulate number emissions.